Evaluating business simulation software: approach, tools and pedagogy - Melanie King; Richard Newman (2009)
Purpose - To identify a business simulation appropriate for MEng Engineering students. The selection was based on the following factors; exploring methods for evaluating potential software and enhancing the learner experience. Design/methodology/approach - An interdisciplinary project team was formed to try and resolve the pedagogic, technical and business aspects that would need to be addressed in order to implement such software within the programme. Tools included a questionnaire to assess the potential enhancement of employability skills and a usability questionnaire on ease of use. These were supplemented with discourse on technical and pedagogic issues. Findings - After the initial scoping study, our findings indicated that two business simulation software packages had potential. These were ‘Marketplace - Venture Strategy’ and ‘SimVenture’. Marketplace proved to be the most suitable in terms of the pedagogic and technical requirements. Research limitations / implications - We were not able to fully trial each simulation over the recommended duration of play because of practical time constraints and we did not have any student contribution to the process. Findings will need to be verified with the piloting cohort of students. Further pedagogic research could be carried out to evidence the enhancement to the student learning experience. Originality/value - This study is valuable because it purposefully uses an interdisciplinary team comprising expertise in; teaching and learning, technology, business and sector knowledge. This was vital in the decision making process. Development of generic methods and tools to measure and evaluate software suitability in relation to usability and employability skills.